The piano owners guide. - Schmeckel, Carl D. (New York Charles Scribners sons, 1974)
Piano owners and buyers are well-advised to read up on their subject. Theres far too much of quick process of buying a new car, and nowhere near enough considering some very tricky artistic/aesthetic issues. This book is a good complement to Larry Fines "The Piano Book" which discusses pianos by brand. Here, the mechanics of a piano are discussed, including the ones that are likely to give you trouble, such as tuning
Keywords: Culture